2018
DOI: 10.1111/psyp.13283
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the conditioned response: A comparison of pupillometry, skin conductance, and startle electromyography

Abstract: In human fear conditioning studies, different physiological readouts can be used to track conditioned responding during fear learning. Commonly employed readouts such as skin conductance responses (SCR) or startle responses have in recent years been complemented by pupillary readouts, but to date it is unknown how pupillary readouts relate to other measures of the conditioned response. To examine differences and communalities among pupil responses, SCR, and startle responses, we simultaneously recorded pupil d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 70 publications
6
54
1
Order By: Relevance
“…We found that learning about CS-US associations was expressed in stronger pupil dilation toward the CS+ relative to the CS-throughout the experiment. The assumption that change in pupil diameter is prone to early habituation was not observed in the present study (see also Leuchs, Schneider, & Spoormaker, 2018). Our finding showing increased pupil dilation to appetitive conditioned stimuli is therefore in accordance with previous findings, but the first to affirm pupil dilation as a conditioned response throughout the experiment in a design focused on appetitive classical conditioning using primary reinforcement in the established preoutcome time window.…”
Section: Increased Pupil Dilation Towards Appetitive Conditioned Stsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that learning about CS-US associations was expressed in stronger pupil dilation toward the CS+ relative to the CS-throughout the experiment. The assumption that change in pupil diameter is prone to early habituation was not observed in the present study (see also Leuchs, Schneider, & Spoormaker, 2018). Our finding showing increased pupil dilation to appetitive conditioned stimuli is therefore in accordance with previous findings, but the first to affirm pupil dilation as a conditioned response throughout the experiment in a design focused on appetitive classical conditioning using primary reinforcement in the established preoutcome time window.…”
Section: Increased Pupil Dilation Towards Appetitive Conditioned Stsupporting
confidence: 93%
“…Previous studies showed both significant SCR effects during appetitive conditioning (Andreatta & Pauli, ; Ebrahimi et al, ; Klucken et al, , , ; Tapia León et al, ), as well as no significant differential response to the conditioned CS (Ebrahimi et al, ; Klucken et al, ; Stussi et al, ; van den Akker et al, ). Our nonsignificant finding may result from insufficient statistical power (especially due to the exclusion of eight participants from the SCR analysis) or habituation effects (i.e., a decrement in response amplitude with repeated CS presentation), which particularly afflicts experiments with a longer duration as used in our study (Leuchs et al, ; Lonsdorf et al, ). Although the acoustically evoked PAR has been suggested as a sensitive index of appetitive responding (Ebrahimi et al, ; Sandt et al, ; Stussi et al, ), the present study could not replicate this.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, participants are sometimes not provided any information at all about the contingencies in the task (i.e., uninstructed fear conditioning; e.g., Haaker et al, 2015;Leuchs, Schneider, & Spoormaker, 2018;Miskovic & Keil, 2013;Sjouwerman, Niehaus, Kuhn, & Lonsdorf, 2016). In the current study, we assessed the effect of these three different types of contingency instructions (i.e., precise contingency instructions, general contingency instructions, and no contingency instructions) on psychophysiological discrimination between the CS+ (i.e., the CS paired with the US) and the CS-(i.e., the CS not paired with the US) at the end of the acquisition phase, and contingency awareness rates as assessed with a retrospective questionnaire.…”
Section: Contingency Instructionsmentioning
confidence: 99%
“…Other measures include pupil size response (PSR) (Korn et al 2017), phasic bradycardia (Castegnetti et al 2016) and respiration amplitude responses . While all of these measures differ between CS+ and CS− in standard fear conditioning and retention, trial-by-trial trajectories suggest they may relate to different underlying components of the learning process (Li et al 2011;Zhang et al 2016;Bach et al 2018b;Leuchs et al 2019, for review, see Ojala and Bach 2019). Also, they appear to be differentially affected by pharmacological interventions targeting consolidation (Bach et al 2018b) and reconsolidation (Soeter and Kindt 2010).…”
mentioning
confidence: 99%